2018
DOI: 10.2147/copd.s148735
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea, COPD, the overlap syndrome, and mortality: results from the 2005–2008 National Health and Nutrition Examination Survey

Abstract: ObjectiveThe aim of this study was to investigate the role of obstructive sleep apnea (OSA) on all-cause mortality in patients with COPD.MethodsData for this cross-sectional study were obtained from the National Health and Nutrition Examination Survey (NHANES) data (year 2005–2008). Eligible subjects were ≥20 years who had no COPD or OSA (n=9,237), had only OSA (n=366), had only COPD (n=695), and had OSA/COPD overlap syndrome (n=90). Univariate and multivariate analyses were used to evaluate factors associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 36 publications
1
34
0
3
Order By: Relevance
“…As outcomes are concerned, early studies reported lower PaO 2 and higher PaCO 2 in overlap patients compared to OSA patients with a similar AHI, associated with higher pulmonary artery pressure at rest and during exercise [112]. More recent observational studies reported increased mortality in overlap patients compared to OSA patients [113115], and a protective effect of CPAP treatment [113, 116, 117]. By contrast, a complex study in over 6,000 subjects from the general population recently reported that mortality was higher in patients with SDB defined as AHI≥5, but occurrence of SDB and SDB severity could mitigate the effects of decreasing FEV 1 on mortality [118].…”
Section: Common Comorbidities In Osa Patientsmentioning
confidence: 99%
“…As outcomes are concerned, early studies reported lower PaO 2 and higher PaCO 2 in overlap patients compared to OSA patients with a similar AHI, associated with higher pulmonary artery pressure at rest and during exercise [112]. More recent observational studies reported increased mortality in overlap patients compared to OSA patients [113115], and a protective effect of CPAP treatment [113, 116, 117]. By contrast, a complex study in over 6,000 subjects from the general population recently reported that mortality was higher in patients with SDB defined as AHI≥5, but occurrence of SDB and SDB severity could mitigate the effects of decreasing FEV 1 on mortality [118].…”
Section: Common Comorbidities In Osa Patientsmentioning
confidence: 99%
“…212,213 ). OSA is a common condition and increases mortality in COPD patients 214 . We therefore recommend polygraphy prior to dNIV initiation 214 .…”
Section: Domiciliary Non-invasive Ventilationmentioning
confidence: 99%
“…Additionally, it was demonstrated that patients with the OS have increased sympathetic activity, which makes them more liable for cardiac complications [37]. Hence, the inflammatory and oxidative stress pathways together can be critical to the serious clinical consequences observed in COPD and OSA when they coexist in the same patient [38].…”
Section: Pathophysiologymentioning
confidence: 99%